Challenges of Citizen Training in Today's Society (Docentes 2.0 Journal, 2024)
Citizenship education must be considered a priority in the world due to globalization. The main objective of this essay was to identify the main challenges for citizenship education in today's society. Likewise, the interpretive paradigm was based on a qualitative approach with a narrative topic design. Through an exhaustive analysis of experiences in various educational contexts, it is emphasized that citizenship must be understood as an active and responsible exercise, which requires acquiring knowledge about rights and duties and respecting others. The difficulties identified include the need for more adequate teacher training and the absence of national policies that strengthen civic education. In conclusion, strengthening citizenship education is crucial to promote democratic and fair societies, and it is essential that civic education becomes a priority within the educational system to face the complexity of today's world and encourage the active participation of citizens.
Keywords: Citizenship; citizenship training; world citizen; creative citizenship